A black color paste for spandex and preparation method thereof
Patent Information
- Application Number
- CN202411793502.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The existing black paste for spandex is difficult to disperse evenly during the dyeing process, which may damage the fiber structure and affect the elasticity and color uniformity of spandex.
The modified medium- and high-color tank method carbon black was used to form a uniform polar film by modification of 3-glycidyl ether oxypropyl trimethoxysilane and dopamine, which improved the dispersion of carbon black in N,N-dimethylacetamide solvent, and interacted with the dispersion stabilizer through hydrogen bonds and van der Waals bonds to enhance dispersion stability and color fastness.
The stability and color fastness of the black color paste for spandex is significantly improved, and the problems of color spots and color difference in spandex fibers are reduced, ensuring excellent uniformity and performance during the dyeing process.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of black color paste for spandex and a preparation method thereof, and in particular to a black color paste for spandex and a preparation method thereof. Background Art
[0002] Spandex, as a high-performance synthetic fiber, plays a pivotal role in the textile industry with its excellent elastic recovery rate and good wear resistance. It is often used to make clothing that requires high stretchability, such as sportswear, tights, swimsuits and socks, providing wearers with unparalleled comfort and freedom. However, when it comes to coloring spandex fabrics, especially dyeing with black color paste, this process requires not only precise technical control, but also a deep understanding of the material properties to ensure that the final product has uniform color, excellent fastness and does not affect the original elasticity of the spandex.
[0003] Black color paste, as a key material in the dyeing process, is usually composed of pigments or dyes, dispersants, thickeners, wetting agents and other ingredients, and is specially designed for dark colors, especially black dyeing. However, most color pastes on the market are water-based, and the dispersion medium is water, which is not suitable for spandex systems. Therefore, when selecting black color paste for spandex, special attention should be paid to its dispersibility and compatibility with spandex fibers. A mild black color paste that can be effectively dispersed in water should be selected to avoid damaging the fiber structure and affecting the elasticity during the dyeing process. In view of this, we propose a black color paste for spandex and a preparation method thereof. Summary of the invention
[0004] The object of the present invention is to provide a black color paste for spandex and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides a black color paste for spandex, comprising the following components: 21-25 parts by weight of modified medium-high pigment tank carbon black, 48-55 parts by weight of N,N-dimethylacetamide, 12-24 parts by weight of a dispersion stabilizer, and 5-12 parts by weight of a polyoxyethylene ether wetting agent;
[0006] Among them, the modified medium and high pigment tank carbon black is obtained by modifying the medium and high pigment tank carbon black with 3-glycidyloxypropyltrimethoxysilane and dopamine in a mass ratio of 1:2-5;
[0007] The dispersion stabilizer is one or two or more of polyether-modified styrene acrylic copolymer, polyetheramine-modified styrene acrylic copolymer, polyether-modified styrene maleic anhydride copolymer and polyetheramine-modified styrene maleic anhydride copolymer.
[0008] A unique dispersion stabilizer is used. Since polyether-modified styrene acrylic copolymer, polyetheramine-modified styrene acrylic copolymer, polyether-modified styrene maleic anhydride copolymer and polyetheramine-modified styrene maleic anhydride copolymer contain hydrophilic groups, these hydrophilic groups can interact with the functional groups on the surface of carbon black. Therefore, the surface functional groups of carbon black are more compatible with the dispersion stabilizer, thereby preventing the agglomeration of carbon black particles.
[0009] Preferably, the preparation method of the modified medium-high pigment trough carbon black is as follows:
[0010] The medium and high pigment trough carbon black particles are dispersed in deionized water, and ultrasonically treated for 20-30 minutes to be fully dispersed. Then, the carbon black dispersion is added to the aqueous solution of 3-glycidyloxypropyltrimethoxysilane, and the reaction is stirred for 2-4 hours. The pH value of the carbon black dispersion after coupling is adjusted, and then the dopamine aqueous solution is added, and the reaction is stirred for 6-8 hours. After the reaction is completed, the particles are washed with deionized water and dried in a vacuum drying oven to obtain modified medium and high pigment trough carbon black.
[0011] Dopamine molecules contain catechol structures, which are very active chemical groups that are prone to oxidation reactions. In weakly alkaline environments, catechol structures are more easily oxidized, thereby initiating self-polymerization reactions. When dopamine is exposed to oxygen and weakly alkaline conditions, the catechol structures are first oxidized into quinone structures, and then the quinone structures are connected by CC bonds or CO bonds to form longer polymer chains. The surface of medium-high pigment slot carbon black usually contains a small amount of polar groups such as hydroxyl and carboxyl groups. These groups can interact with the catechol groups in the dopamine molecules through hydrogen bonds or van der Waals forces, promoting the adsorption of dopamine molecules on the carbon black surface. As the polymerization reaction proceeds, dopamine molecules gradually form a three-dimensional network structure and eventually form a uniform film on the surface of carbon black. Since the film formed by dopamine self-polymerization is rich in polar groups, these polar groups significantly increase the overall polarity of the carbon black surface, making the modified carbon black more compatible with polar solvents or matrix materials. The introduction of the dopamine layer not only changes the chemical properties of the carbon black surface, but also prevents direct contact and aggregation between carbon black particles through the steric hindrance effect, thereby improving the dispersion stability of carbon black in various media. Its surface functional groups are also more compatible with dispersion stabilizers, which is beneficial to increasing the solid content and dispersion fluidity of the product.
[0012] However, the polar group content on the surface of medium and high pigment trough carbon black is relatively low, and dopamine is unevenly adsorbed on the carbon black surface, resulting in an uneven film formed by dopamine on the carbon black surface. Therefore, 3-glycidyloxypropyltrimethoxysilane is introduced, and its hydrolysis in water to generate silanol groups forms a covalent bond on the carbon black surface. The other end is further enhanced through hydrogen bonds and van der Waals bonds to further enhance the uniform coverage and adsorption capacity of dopamine on the carbon black surface, thereby promoting dopamine to form a uniform film on the carbon black surface, avoiding the decrease in dispersibility and surface polarity caused by uneven film.
[0013] Preferably, the mass ratio of the medium-high pigment trough carbon black to dopamine is 1:0.1-0.3.
[0014] Preferably, the pH value of the carbon black dispersion after coupling is 7.5-8.5.
[0015] Preferably, the mass fraction of the 3-glycidyloxypropyltrimethoxysilane aqueous solution is 1-5%.
[0016] Preferably, the mass concentration of the dopamine aqueous solution is 2-10 mg / mL.
[0017] Preferably, the water content of the modified medium-high pigment trough carbon black is less than 0.3%.
[0018] On the other hand, the present invention provides a method for preparing a black color paste for spandex, which is used for any one of the black color pastes for spandex described above, comprising the following steps:
[0019] N,N-dimethylacetamide is first added into the chamber of a high-speed mixer, and then a dispersing stabilizer and polyoxyethylene ether are added. The high-speed mixer is started, and the mixture is stirred at a speed of 1000-2000 rpm for 1-3 minutes to fully dissolve the dispersing stabilizer in the N,N-dimethylacetamide. The modified medium-high pigment tank carbon black is then added, and the stirring is continued for 3-5 minutes until the raw materials are fully dispersed and a uniformly wetted initial slurry is formed. The initial slurry is transferred into a grinder, and the grinding medium is zirconium beads with a purity of more than 95%, the diameter of the zirconium beads is 0.8-1.5 mm, and the filling rate is 70-80%. It is ensured that the movement speed of the zirconium beads during grinding is not less than 13 m / s. Grinding is performed 2-4 times, and each grinding time is 30-60 minutes. The ground slurry is filtered through a 1250-mesh filter screen, and the filtered carbon black slurry is placed in a sealed container to obtain a black color paste for spandex.
[0020] N,N-dimethylacetamide, a commonly used solvent in spandex system, is used as the medium of the dispersion system, which is more suitable for the application of spandex system. At the same time, since N,N-dimethylacetamide is a polar solvent and the surface of modified medium and high pigment tank carbon black is polar, according to the principle of like dissolves like, the modified medium and high pigment tank carbon black also has good dispersibility in dimethylacetamide, which can effectively reduce the problems of color spots and color difference on spandex fibers.
[0021] Preferably, the water content of the N,N-dimethylacetamide does not exceed 0.05%, and the scraper fineness of the slurry after grinding is less than 2.5 μm.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] In the black color paste for spandex and the preparation method thereof, modified medium-high pigment slot carbon black is used to prepare a black color paste for spandex, 3-glycidyloxypropyltrimethoxysilane is used to enhance the binding force between the medium-high pigment slot carbon black and organic matter, and the uniform coverage and adsorption capacity of dopamine on the surface of the medium-high pigment slot carbon black are enhanced, and a uniform polar film is formed on the surface of the medium-high pigment slot carbon black through the self-polymerization ability of dopamine, thereby improving the dispersibility of the modified medium-high pigment slot carbon black in N,N-dimethylacetamide solvent, and interacting with a dispersion stabilizer through hydrogen bonds and van der Waals bonds, which is beneficial to improving the solid content and dispersion fluidity of the product, and effectively reducing the problems of color spots and color differences on spandex fibers. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The invention discloses a black color paste for spandex, comprising the following components: 21-25 parts by weight of modified medium-high pigment tank carbon black, 48-55 parts by weight of N,N-dimethylacetamide, 12-24 parts by weight of a dispersion stabilizer, and 5-12 parts by weight of a polyoxyethylene ether wetting agent;
[0026] Among them, the modified medium and high pigment tank carbon black is obtained by modifying the medium and high pigment tank carbon black with 3-glycidyloxypropyltrimethoxysilane and dopamine in a mass ratio of 1:2 to 5.
[0027] The dispersion stabilizer is one or two or more of polyether-modified styrene acrylic copolymer, polyetheramine-modified styrene acrylic copolymer, polyether-modified styrene maleic anhydride copolymer and polyetheramine-modified styrene maleic anhydride copolymer.
[0028] Among them, the dispersion stabilizer is preferably a polyetheramine-modified styrene acrylic copolymer.
[0029] Embodiment 1: A black color paste for spandex and a preparation method thereof, comprising the following steps:
[0030] Prepare the following components: 21 parts by weight of modified medium-high pigment trough carbon black, 55 parts by weight of N,N-dimethylacetamide, 24 parts by weight of polyetheramine-modified styrene acrylic copolymer dispersion stabilizer, and 12 parts by weight of polyoxyethylene ether wetting agent;
[0031] Among them, the modified medium-high pigment tank carbon black is obtained by modifying the medium-high pigment tank carbon black with 3-glycidyloxypropyltrimethoxysilane and dopamine in a mass ratio of 1:2; the mass ratio of the medium-high pigment tank carbon black to dopamine is 1:0.1;
[0032] Disperse medium and high pigment trough carbon black particles in deionized water, treat with ultrasound for 30 minutes to fully disperse, then add the carbon black dispersion to a 1% mass fraction of 3-glycidyloxypropyltrimethoxysilane aqueous solution, stir and react for 2 hours, adjust the pH value of the carbon black dispersion after coupling to 8.5, then add a 5 mg / mL mass concentration of dopamine aqueous solution, stir and react for 6 hours, after the reaction is completed, wash the particles with deionized water, and dry them in a vacuum drying oven with a moisture content of less than 0.3%, to obtain modified medium and high pigment trough carbon black;
[0033] N,N-dimethylacetamide is first added into the chamber of the high-speed mixer, and then the dispersion stabilizer and polyoxyethylene ether are added. The high-speed mixer is started and stirred at a speed of 1500 rpm for 1 minute to make the dispersion stabilizer fully dissolved in the N,N-dimethylacetamide. The modified medium and high pigment tank carbon black is then added and stirred for 3 minutes until the raw materials are fully dispersed and a uniformly wetted initial slurry is formed. The initial slurry is transferred to a grinder. The grinding medium is zirconium beads with a purity of more than 95%, the diameter of the zirconium beads is 1.5 mm, and the filling rate is 70%. It is ensured that the movement speed of the zirconium beads during grinding is not less than 13 m / s. Grinding is performed 3 times, and each grinding time is 30 minutes. The ground slurry is filtered through a 1250-mesh filter screen, and the filtered carbon black slurry is placed in a sealed container to obtain a black color paste for spandex.
[0034] Embodiment 2: A black color paste for spandex and a preparation method thereof, comprising the following steps:
[0035] Prepare the following components: 23 parts by weight of modified medium-high pigment trough carbon black, 55 parts by weight of N,N-dimethylacetamide, 24 parts by weight of polyetheramine-modified styrene acrylic copolymer dispersion stabilizer, and 12 parts by weight of polyoxyethylene ether wetting agent;
[0036] Among them, the modified medium-high pigment tank carbon black is obtained by modifying the medium-high pigment tank carbon black with 3-glycidyloxypropyltrimethoxysilane and dopamine at a mass ratio of 1:3; the mass ratio of the medium-high pigment tank carbon black to dopamine is 1:0.2;
[0037] Disperse medium and high pigment trough carbon black particles in deionized water, treat with ultrasound for 30 minutes to fully disperse, then add the carbon black dispersion to a 1% mass fraction of 3-glycidyloxypropyltrimethoxysilane aqueous solution, stir and react for 2 hours, adjust the pH value of the carbon black dispersion after coupling to 8.5, then add a 5 mg / mL mass concentration of dopamine aqueous solution, stir and react for 6 hours, after the reaction is completed, wash the particles with deionized water, and dry them in a vacuum drying oven with a moisture content of less than 0.3%, to obtain modified medium and high pigment trough carbon black;
[0038] N,N-dimethylacetamide is first added into the chamber of the high-speed mixer, and then the dispersion stabilizer and polyoxyethylene ether are added. The high-speed mixer is started and stirred at a speed of 1500 rpm for 1 minute to make the dispersion stabilizer fully dissolved in the N,N-dimethylacetamide. The modified medium and high pigment tank carbon black is then added and stirred for 3 minutes until the raw materials are fully dispersed and a uniformly wetted initial slurry is formed. The initial slurry is transferred to a grinder. The grinding medium is zirconium beads with a purity of more than 95%, the diameter of the zirconium beads is 1.5 mm, and the filling rate is 70%. It is ensured that the movement speed of the zirconium beads during grinding is not less than 13 m / s. Grinding is performed 3 times, and each grinding time is 30 minutes. The ground slurry is filtered through a 1250-mesh filter screen, and the filtered carbon black slurry is placed in a sealed container to obtain a black color paste for spandex.
[0039] Embodiment 3: A black color paste for spandex and a preparation method thereof, comprising the following steps:
[0040] Prepare the following components: 25 parts by weight of modified medium-high pigment trough carbon black, 55 parts by weight of N,N-dimethylacetamide, 24 parts by weight of polyetheramine-modified styrene acrylic copolymer dispersion stabilizer, and 12 parts by weight of polyoxyethylene ether wetting agent;
[0041] Among them, the modified medium-high pigment tank carbon black is obtained by modifying the medium-high pigment tank carbon black with 3-glycidyloxypropyltrimethoxysilane and dopamine at a mass ratio of 1:5; the mass ratio of the medium-high pigment tank carbon black to dopamine is 1:0.3;
[0042] Disperse medium and high pigment trough carbon black particles in deionized water, treat with ultrasound for 30 minutes to fully disperse, then add the carbon black dispersion to a 1% mass fraction of 3-glycidyloxypropyltrimethoxysilane aqueous solution, stir and react for 2 hours, adjust the pH value of the carbon black dispersion after coupling to 8.5, then add a 5 mg / mL mass concentration of dopamine aqueous solution, stir and react for 6 hours, after the reaction is completed, wash the particles with deionized water, and dry them in a vacuum drying oven with a moisture content of less than 0.3%, to obtain modified medium and high pigment trough carbon black;
[0043] N,N-dimethylacetamide is first added into the chamber of the high-speed mixer, and then the dispersion stabilizer and polyoxyethylene ether are added. The high-speed mixer is started and stirred at a speed of 1500 rpm for 1 minute to make the dispersion stabilizer fully dissolved in the N,N-dimethylacetamide. The modified medium and high pigment tank carbon black is then added and stirred for 3 minutes until the raw materials are fully dispersed and a uniformly wetted initial slurry is formed. The initial slurry is transferred to a grinder. The grinding medium is zirconium beads with a purity of more than 95%, the diameter of the zirconium beads is 1.5 mm, and the filling rate is 70%. It is ensured that the movement speed of the zirconium beads during grinding is not less than 13 m / s. Grinding is performed 3 times, and each grinding time is 30 minutes. The ground slurry is filtered through a 1250-mesh filter screen, and the filtered carbon black slurry is placed in a sealed container to obtain a black color paste for spandex.
[0044] Embodiment 4: A black color paste for spandex and a preparation method thereof, comprising the following steps:
[0045] Prepare the following components: 25 parts by weight of modified medium-high pigment trough carbon black, 48 parts by weight of N,N-dimethylacetamide, 12 parts by weight of polyetheramine-modified styrene acrylic copolymer dispersion stabilizer, and 5 parts by weight of polyoxyethylene ether wetting agent;
[0046] Among them, the modified medium-high pigment tank carbon black is obtained by modifying the medium-high pigment tank carbon black with 3-glycidyloxypropyltrimethoxysilane and dopamine at a mass ratio of 1:5; the mass ratio of the medium-high pigment tank carbon black to dopamine is 1:0.3;
[0047] Disperse medium and high pigment trough carbon black particles in deionized water, treat with ultrasound for 30 minutes to fully disperse, then add the carbon black dispersion to a 1% mass fraction of 3-glycidyloxypropyltrimethoxysilane aqueous solution, stir and react for 2 hours, adjust the pH value of the carbon black dispersion after coupling to 8.5, then add a 5 mg / mL mass concentration of dopamine aqueous solution, stir and react for 6 hours, after the reaction is completed, wash the particles with deionized water, and dry them in a vacuum drying oven with a moisture content of less than 0.3%, to obtain modified medium and high pigment trough carbon black;
[0048] N,N-dimethylacetamide is first added into the chamber of the high-speed mixer, and then the dispersion stabilizer and polyoxyethylene ether are added. The high-speed mixer is started and stirred at a speed of 1500 rpm for 1 minute to make the dispersion stabilizer fully dissolved in the N,N-dimethylacetamide. The modified medium and high pigment tank carbon black is then added and stirred for 3 minutes until the raw materials are fully dispersed and a uniformly wetted initial slurry is formed. The initial slurry is transferred to a grinder. The grinding medium is zirconium beads with a purity of more than 95%, the diameter of the zirconium beads is 1.5 mm, and the filling rate is 70%. It is ensured that the movement speed of the zirconium beads during grinding is not less than 13 m / s. Grinding is performed 3 times, and each grinding time is 30 minutes. The ground slurry is filtered through a 1250-mesh filter screen, and the filtered carbon black slurry is placed in a sealed container to obtain a black color paste for spandex.
[0049] Comparative Example 1: The method of Example 3 was adopted, and medium-high pigment trough process carbon black was directly added without modification.
[0050] Comparative Example 2: The method of Example 3 was adopted, and only 3-glycidyloxypropyltrimethoxysilane was used to modify the medium and high pigment tank carbon black.
[0051] Comparative Example 3: The method of Example 3 was adopted, and only dopamine was used to modify the medium and high pigment trough carbon black.
[0052] The present invention adopts modified medium and high pigment tank carbon black to prepare a black color paste for spandex, wherein the performance index inspection items and inspection standards of the black color paste for spandex are as follows:
[0053] In order to test the stability of the color paste, the color paste was placed at 50°C and 90% RH, and samples were taken on the 1st and 14th days to test the solid content of the upper liquid. The solid content of the upper liquid was compared and the change in solid content was calculated. The change in solid content = (solid content on the 1st day - solid content on the 14th day) / solid content on the 1st day × 100%. The smaller the change in solid content, the slower the sedimentation rate, which is more conducive to production and storage.
[0054] According to GB / T3920-2008 "Textiles - Colour Fastness - Colour Fastness to Rubbing", the spandex spinning stock solution is first matured and then black colour paste is added to obtain black spandex spinning stock solution, black spandex fiber is prepared by dry spinning technology, and the black spandex fiber is woven into black cloth by a pole loom. The black cloth is then evaluated for its wet and dry rubbing fastness level under standard light source using GB / T251-2008 "Textiles - Colour Fastness - Grey Scale for Assessing Staining".
[0055] Place the fabric flat on the test bench, calibrate the spectrophotometer with a standard white board, adjust the light source type to D65 according to the instrument manual, and the observation angle to 10°. Mark 9 evenly distributed test points on the fabric, including the edge and center areas, to fully reflect the uniform dyeing of the fabric. Measure each test point 3 times, take the average value as the color data of the point, record the L* (brightness), a* (red-green axis), and b* (yellow-blue axis) values of each test point, and calculate the color difference ΔE*=[(L1−L0) 2 + (a1−a0) 2 +(b1−b0) 2 ] 1 / 2 , where L1, a1, b1 and L0, a0, b0 are the L*, a*, b* values of the two test points respectively. The average ΔE value of all test points is calculated. If the average ΔE value of all test points is less than 1.0, it can be considered that the fabric has good levelness of dyeing.
[0056] According to the above standards, a black color paste for spandex prepared in the above Examples 1-4 and Comparative Examples 1-3 was tested, and the obtained data are shown in Table 1:
[0057] Table 1 Performance data of Examples 1-4 and Comparative Examples 1-3
[0058]
[0059] The above data fully show that compared with Comparative Examples 1-3, Examples 1-4 can fully show the effect of the modified medium and high pigment tank carbon black on the stability, color fastness and color difference performance of the black color paste for spandex.
[0060] Since the black color paste for spandex is prepared by using modified medium-high pigment tank carbon black, the performance of the black color paste for spandex is effectively improved by modifying the medium-high pigment tank carbon black, as follows:
[0061] It can be seen from Examples 1-3 that with the continuous increase in the content and component ratio of the modified medium and high pigment tank carbon black, the stability, color fastness and color difference performance of the black color paste for spandex are significantly improved. This is because 3-glycidyloxypropyltrimethoxysilane and dopamine can effectively improve the surface properties of carbon black, making it more compatible with the dispersion medium N,N-dimethylacetamide and reducing the agglomeration of carbon black particles. This not only improves the stability of the color paste, but also because the carbon black particles are more evenly distributed, making the color of the spandex fiber more uniform during dyeing, and the color fastness and color difference are higher.
[0062] It can be seen from Examples 3 and 4 that as the contents of other components of the black color paste for spandex continue to change, the stability, color fastness and color difference performance of the black color paste for spandex do not change significantly. This is because the modified medium-high pigment trough carbon black is the most important component in the color paste, and its content and degree of modification play a decisive role in the performance of the color paste. The content of the modified medium-high pigment trough carbon black remains unchanged, so its dispersibility and coloring properties in the color paste are basically the same.
[0063] According to the above test experiments, the black color paste for spandex prepared according to Example 3 has the best performance, so Example 3 is taken as the best example;
[0064] By comparing Example 3 with Comparative Examples 1-3, it can be seen that:
[0065] In Comparative Example 1, medium-high pigment trough carbon black is directly added without modification. The stability, color fastness and color difference performance of the black color paste for spandex are worse. This is because there are too few polar groups on the surface of medium-high pigment trough carbon black, which are insufficient to make it evenly dispersed in N,N-dimethylacetamide. It is easy to agglomerate to form larger aggregates, resulting in poor dispersion of the color paste, affecting the long-term stability, color fastness and color difference of the color paste.
[0066] In Comparative Example 2, only 3-glycidyloxypropyltrimethoxysilane is used to modify the medium and high pigment tank carbon black. The black color paste for spandex has poor stability, color fastness and color difference performance. This is because 3-glycidyloxypropyltrimethoxysilane is hydrolyzed to generate silanol groups, which form covalent bonds with the polar groups on the surface of carbon black, thereby forming a modified layer on the surface of carbon black. However, it does not have the self-polymerization ability of dopamine, and cannot form a uniform and polar group-rich film on the surface of carbon black. It also uses the steric hindrance effect to prevent direct contact and aggregation between carbon black particles. Therefore, the carbon black particles are insufficiently dispersed in the color paste, which leads to poor stability, low color fastness and large color difference.
[0067] In Comparative Example 3, only dopamine was used to modify the medium- and high-pigment trough-process carbon black. The stability, color fastness and color difference performance of the black color paste for spandex were worse. This was because dopamine was prone to self-polymerization in a weakly alkaline environment to form a film rich in polar groups. This film could indeed increase the polarity of the carbon black surface and help improve the dispersion of carbon black in the solvent. The medium- and high-pigment trough-process carbon black had a small number of active sites on its surface, which would cause an uneven film formed by dopamine on the carbon black surface. Therefore, the surface polarity was insufficient, the dispersion was insufficient, and the stability was poor.
[0068] In summary, a black color paste for spandex was prepared by modifying medium and high pigment slot carbon black, 3-glycidyloxypropyltrimethoxysilane was used to increase the active sites on the surface of medium and high pigment slot carbon black, and dopamine self-polymerized on the surface of medium and high pigment slot carbon black to form a uniform polar film, thereby improving the dispersibility and stability of medium and high pigment slot carbon black.
[0069] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments, and the above embodiments and descriptions are only preferred examples of the present invention, and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A black color paste for spandex, characterized in that: The invention comprises the following components: 21-25 parts by weight of modified medium-high pigment trough carbon black, 48-55 parts by weight of N,N-dimethylacetamide, 12-24 parts by weight of a dispersion stabilizer and 5-12 parts by weight of a polyoxyethylene ether wetting agent; Among them, the modified medium-high pigment tank carbon black is obtained by modifying the medium-high pigment tank carbon black with 3-glycidyloxypropyltrimethoxysilane and dopamine in a mass ratio of 1:2-5; The dispersion stabilizer is one or two or more of polyether-modified styrene acrylic copolymer, polyetheramine-modified styrene acrylic copolymer, polyether-modified styrene maleic anhydride copolymer and polyetheramine-modified styrene maleic anhydride copolymer; The preparation method of the modified medium-high pigment trough carbon black is as follows: Disperse medium-high pigment tank carbon black particles in deionized water, treat with ultrasound for 20-30 minutes to fully disperse, then add the carbon black dispersion to the aqueous solution of 3-glycidyloxypropyltrimethoxysilane, stir and react for 2-4 hours, adjust the pH value of the carbon black dispersion after coupling, then add the dopamine aqueous solution, stir and react for 6-8 hours, after the reaction is completed, wash the particles with deionized water, and dry them in a vacuum drying oven to obtain modified medium-high pigment tank carbon black; The pH value of the carbon black dispersion after coupling is 7.5-8.
5.
2. The black color paste for spandex according to claim 1, characterized in that: The mass ratio of the medium-high pigment trough carbon black to dopamine is 1:0.1-0.
3.
3. The black color paste for spandex according to claim 1, characterized in that: The mass fraction of the 3-glycidyloxypropyltrimethoxysilane aqueous solution is 1-5%.
4. The black color paste for spandex according to claim 1, characterized in that: The mass concentration of the dopamine aqueous solution is 2-10 mg / mL.
5. The black color paste for spandex according to claim 1, characterized in that: The water content of the modified medium-high pigment channel carbon black is less than 0.3%.
6. A method for preparing a black color paste for spandex, used for preparing a black color paste for spandex according to any one of claims 1 to 5, characterized in that: The steps include: N,N-dimethylacetamide is first added into the chamber of a high-speed mixer, and then a dispersing stabilizer and polyoxyethylene ether are added. The high-speed mixer is started, and the mixture is stirred at a speed of 1000-2000 rpm for 1-3 minutes to fully dissolve the dispersing stabilizer in the N,N-dimethylacetamide. The modified medium-high pigment tank carbon black is then added, and the stirring is continued for 3-5 minutes until the raw materials are fully dispersed and a uniformly wetted initial slurry is formed. The initial slurry is transferred into a grinder, and the grinding medium is zirconium beads with a purity of more than 95%, the diameter of the zirconium beads is 0.8-1.5 mm, and the filling rate is 70-80%. It is ensured that the movement speed of the zirconium beads during grinding is not less than 13 m / s. The grinding is performed 2-4 times, and the grinding time for each time is 30-60 minutes. The ground slurry is filtered through a 1250-mesh filter screen, and the filtered carbon black slurry is placed in a sealed container to obtain a black color paste for spandex.
7. The method for preparing a black color paste for spandex according to claim 6, characterized in that: The water content of the N,N-dimethylacetamide does not exceed 0.05%, and the scraper fineness of the slurry after grinding is less than 2.5 μm.
Citation Information
Patent Citations
Method for producing polyether black spandex fibers
CN101984158A
High-fixation carbon black inorganic coating and preparation method thereof
CN117645808A